Barriers and facilitators to implementing a new regulation restricting antimicrobial use in dairy production in Québec, Canada: A qualitative study - Millar, Nikky; Dufour, Simon; Lardé, Hélène; Roy, Jean-Philippe; Belloc, Catherine; Francoz, David; Paradis, Marie-Ève; Archambault, Marie; Fairbrother, John Morris; Aenishaenslin, Cécile (Frontiers in Veterinary Science, 2023)
With the emergence of antimicrobial resistance (AMR), many countries are implementing restrictive regulations to reduce antimicrobial use (AMU) in animal production. Although these measures are effective at the national level, their implementation may generate challenges for producers and veterinarians. The objective of this study was to explore the barriers and facilitators of implementing a new regulation restricting the use of antimicrobials of very high importance for human health in the dairy production sector in the province of Québec, Canada. Individual interviews were conducted with fifteen veterinarians and twenty-seven dairy producers. Thematic analysis was performed based on the COM-B model of behaviour change (capability-opportunity-motivation-behaviour). Our results indicated that the lack of availability of alternative treatments, the long delays related to diagnostic tests and the fear of economic consequences were major barriers to the implementation of the regulation. A small number of producers also perceived that the regulation negatively impacted the health and wellbeing of their animals. Additionally, participants acknowledged the importance of early education and training to better understand the purpose of the regulation and increase its acceptability. Lastly, most participants reported that they had not only reduced their use of antimicrobials of high human health importance following the regulation, but they had also increased preventive practices on their farm. This study reveals that the implementation of restrictive regulations to reduce AMU in animal production can lead to multiple challenges in practice. Our results highlight the need for better communication and training of producers and veterinarians before and during the implementation of similar regulations in the future and underline the importance of measuring the direct and indirect impacts of those regulations on productivity and on animal health and wellbeing.